2018
DOI: 10.1177/0145445518794368
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Literature on the Functional Analysis of Inappropriate Mealtime Behavior

Abstract: A functional analysis is a well-established and widely used assessment in the treatment of challenging behavior. Given the fact that functional analysis results can inform treatment selection and procedures, a review of the current literature regarding functional analysis of inappropriate mealtime behavior (IMB) is warranted as it may guide researchers in conducting a functional analysis prior to treating IMB. This review summarizes the literature regarding functional analysis of IMB. Fourteen studies that imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
10
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 37 publications
1
10
2
Order By: Relevance
“…In addition, the trial‐based functional analysis identified a similar percentage of cases to be multiply maintained by escape and attention (29% compared to 20% ‐ 48%), whereas the extended functional analysis identified more cases to be multiply maintained by escape and attention (71% compared to 20% ‐ 48%). Unlike previous studies, which found attention to be the sole maintaining variable in 0% ‐ 2% of cases (Hodges et al, 2020; Saini, Jessel, et al, 2019; Saini, Kadey, et al, 2019), the trial‐based functional analysis in this study found attention to be the sole maintaining variable for 29% of cases. It is important to note that this study and previous studies evaluating the maintaining variables of inappropriate mealtime behavior may not be representative of the overall pediatric feeding disorders population.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…In addition, the trial‐based functional analysis identified a similar percentage of cases to be multiply maintained by escape and attention (29% compared to 20% ‐ 48%), whereas the extended functional analysis identified more cases to be multiply maintained by escape and attention (71% compared to 20% ‐ 48%). Unlike previous studies, which found attention to be the sole maintaining variable in 0% ‐ 2% of cases (Hodges et al, 2020; Saini, Jessel, et al, 2019; Saini, Kadey, et al, 2019), the trial‐based functional analysis in this study found attention to be the sole maintaining variable for 29% of cases. It is important to note that this study and previous studies evaluating the maintaining variables of inappropriate mealtime behavior may not be representative of the overall pediatric feeding disorders population.…”
Section: Discussioncontrasting
confidence: 93%
“…In comparison to other studies reviewing the maintaining variables of inappropriate mealtime behavior (Hodges et al, 2020; Saini, Jessel, et al, 2019; Saini, Kadey, et al, 2019), we found a lower percentage of children's inappropriate mealtime behavior was maintained by only escape (14% from trial‐based and extended functional analyses compared to 33% ‐ 80%). In addition, the trial‐based functional analysis identified a similar percentage of cases to be multiply maintained by escape and attention (29% compared to 20% ‐ 48%), whereas the extended functional analysis identified more cases to be multiply maintained by escape and attention (71% compared to 20% ‐ 48%).…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…NRS increases consumption of nutritive foods by eliminating the negative reinforcement contingency (i.e., escape from the bite or meal) that maintains IMB. This is accomplished by keeping the spoon at the midline of the child's lips until they accept the bite (e.g., Hodges et al, 2020). However, NRS may produce short-term increases in IMB such as extinction bursts (e.g., Piazza et al, 2003;Woods & Borrero, 2019) and aggression (e.g., Bachmeyer, 2009).…”
mentioning
confidence: 99%